From Oral to Digital: The Reconstruction of Folk Tales in Malaysia: (Daripada Cetak Kepada Digital: Rekonstruksi Cerita Rakyat di Malaysia) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2019)
In line with the development in technology, folk literature has evolved from oral to print and subsequently entered into the digital space, enriching its style and presentation to meet various needs. However, in the twentieth century, many folklore experts, especially in the West, felt that the introduction of modern technology would stamp out folklore. A few others, on the other hand, anticipated that the tradition would advance into cyberspace. What is the situation for Malay folk literature in Malaysia? This study aims to examine whether the transformation of folklore in Malaysia is in line with technological developments and the introduction of the National Creative Industry Policy. This study is primarily aimed at investigating the amount of Malay folk literature published through digital media and examining the formats used by local publishers. The result of this study are that the folklore ecosystem in Malaysia has been very slow to develop and that urgent efforts are needed to ensure that folk literature, being a national treasure, can be preserved and its status elevated.Keywords: Folk tales, digital replica books, interactive digital books, ePub, APK, PDF